KARAKTERISTIK PENGERINGAN BIJI PINANG MENGGUNAKAN EXPERIMENTAL DRYER - Tori Yigibalom; Lady C. CH. E. Lengkey; Ireine A. Longdong (Universitas Sam Ratulangi, 2023)
Abstract Areca nut seeds at harvest generally have a high water content, so to reduce the water content of betel nuts, namely drying or drying the betel nuts, they must be dried because if they contain high water content, the betel nuts will be easily damaged. To obtain the drying characteristics, thick sliced, medium sliced, and thin sliced areca seed layers were dried using an experimental dryer. This study aims to analyze temperature changes in the dryer during the drying process, determine the drying characteristics of areca nut meat including moisture content versus time, drying rate versus time and drying rate versus moisture content. The betel nut meat taken from the Malalayang One area is then sliced into 3 thicknesses, namely thick, medium and thin. Observations of temperature changes were carried out at the temperature of the material in each thickness, the ambient temperature, the plenum temperature and the temperature above the dried material. The temperature data is plotted and analyzed graphically. The water content was analyzed descriptively calculated based on the hourly weight loss. drying rate obtained from calculations and analyzed graphically. The results showed the temperature distribution in the plenum room, drying room, material temperature and drying room temperature. The water content decreased inversely with the change in time, the longer the drying time, the lower the water content in Areca seed, showing a pattern of decreasing water content in this experiment by showing an exponential pattern. Drying time for Areca nut seeds using this drying tool takes 9, 5, and 4 hours for thick, medium, and thin slices. The moisture content of Areca seed at the end of drying was 9.0%, 4.8% and 3.07 for thick, medium and thin slices, respectively. The drying rate of Areca seed relative to the drying time decreased the drying rate. The average drying rates for thick, medium, and thin slices were 7.92%/hour, 15.10%/hour, and 19.31%/hour, respectively. Keywords : Drying, Areca Nut, Experimental Dryer